Effect of mycorrhizal inoculation and phosphorus fertilizer on maize root infectivity in three soil series - Aboderin Adebimpe A.; Oyediran Gbade O. (Journal of Agricultural Sciences (Belgrade))
An experiment was carried out to examine the influence of mycorrhizal inoculation and phosphorus fertilizer on maize root infectivity in three soil series at the Ladoke Akintola University of Technology (LAUTECH), Ogbomoso, Nigeria. The treatments included three soil series (Gambari, Itagunmodi and Iwo series), three levels of phosphorus fertilizer (0, 30 and 60 kg P2O5/ha) and three levels of mycorrhizal inoculation (0, 10 and 20 g per 15 kg soil). The experimental design used was a 3×3×3 factorial trial in a completely randomized design with three replications. Root infectivity was evaluated by the grid line intersect method. After harvesting, the phosphorus (P) uptake was determined by multiplying the P concentration in the plant by the total dry weight. The data were analyzed using analysis of variance and the significant means of the treatment were compared using the Duncan's multiple range test at the 5% significance level. The results revealed that P uptake was influenced significantly (p < 0.05) by the soil series. The order of decrease in P uptake across the soil series was as follows: Itagunmodi (0.54 mg/kg) < Iwo (0.90 mg/kg) < Gambari (2.52 mg/kg). Root infectivity significantly enhanced the uptake of P. The highest root infectivity and the highest P uptake were achieved at 20 g inoculation. Mycorrhizal infection levels were reduced by moderate to high rates of soluble phosphorus fertilizer. Thus, increasing levels of phosphate fertilizer stimulate maize root growth but significantly reduce root infection levels.